PENGARUH KREDIT BERMASALAH TERHADAP PROFITABILITAS PADA KELOMPOK BANK BERDASARKAN MODAL INTI (KBMI) IV PERIODE 2019-2020 - Muhamad Azmi Septian, (2021)
Non-Performing Loan is an indicator of the health of a bank's assets in the form of loans that have failed to be paid by the borrower within a certain period of time. In this case, the Bank needs to keep the value of Non-Performing Loans low, by implementing a way of controlling credit risk that is channeled to the public appropriately to minimize bad loans that will occur, while if bad loans cannot be cut off, the bank can maximize the 3R policy, namely rescheduling. , reconditioning and restructuring to increase the value of the Non-Performing Loan, in accordance with Bank Indonesia regulations, where the Bank is said to be healthy when the NPL disincentive parameter is below 5%, because an increase in Non-Performing Loan can affect the income or profitability generated by a Bank. The author aims to determine and calculate the effect of non-performing loans on the level of profitability in the Group of Banks Based on Core Capital (KBMI) IV, namely Bank BCA, Bank BNI, Bank BRI, Bank Mandiri. The data used is the annual report for the period 2019-2020. Based on the results of the study, it shows that non-performing loans measured using the NPL ratio have a significant negative effect on profitability as measured using the ROA ratio, this is evidenced by the t significance value of 0.000 which is smaller than 0.05.